Diversity of phyllostomid bats in riparian vegetation, Tabasco, Mexico - Pérez-Netzahual, Elizabeth; Santiago- Plata, Víctor Manuel; García-Morales, Rodrigo (Ecosistemas y Recursos Agropecuarios, 2023)
The riparian vegetation in the Usumacinta river basin in Tabasco, Mexico is an important ecosystem for the maintenance of biological diversity, unfortunately, it is the most affected by the expansion of livestock and agriculture. Understanding how the diversity of phyllostomid bats is distributed along the riparian vegetation strip is information for decision-making in the conservation of the habitat of the bat community. The study aimed to compare the structure and composition of phyllostomid bat assemblages at different riparian vegetation sites along the Usumacinta River in Tabasco, Mexico. For seven months, phyllostomid bats were captured with four mist nets at six riparian vegetation sites. Bat structure and composition were described and compared between sites based on the effective number of species, rank abundance curves, and complementarity index. A total of 541 individuals comprising 15 species were captured, 67% of the species belong to the subfamily Stenodermatinae. No differences were found between the richness and diversity of phyllostomid bats; however, we did observe differences in assemblage composition between sites. This study provides basic information that will serve in decision-making to conserve bat diversity in riparian vegetation strips in the State and the region.